Exploring Young Learners’ Experiences in Using Duolingo for English Learning in an Islamic Elementary School - Addiningruum, Maulida Fitria; Syahid, Abdul; Mirza, Akhmad Ali (Universitas Pahlawan Tuanku Tambusai, 2025)
Technology requires language teachers to utilize online media, including the internet, websites, social media, and virtual platforms, to enhance teaching and learning. This research focuses on exploring of the Duolingo application on students' English learning. Researchers used qualitative methods to explore students' experiences while learning English with the Duolingo application. The instruments of this research were observation, interviews, and documentation. The study involved 22 students in class 4 of the Islamic Elementary School who expressed positive attitudes toward foreign language learning using the Duolingo online application technology. Learning a foreign language through game-based applications is more effective in fostering enthusiasm for learning, despite complaints from some students who lack internet coverage at home. Researchers hope that, in the future, by conducting this research, English teachers and schools can consider providing technological facilities.